Efektivitas Model Problem-Based Learning pada Mata Pelajaran Instalasi Tenaga Listrik di SMK - Fasraida Daulay; Hansi Effendi (Universitas Negeri Padang, 2020)
This study aims to see the effectiveness of the use of problem-based learning models in Electric Power Installation subject in class XI TITL of SMK Negeri 2 Sijunjung. This research is Pre-Experimental research using one Group Pretest-Posttest design. The research subjects were all students of class XI TITL of SMK Negeri 2 Sijunjung with 30 people and for trials conducted on class XI TITL 1 of SMK Negeri 5 Padang as many as 30 people. The test items for the pretest and posttest were 30 items each. After being analyzed, 23 questions were declared valid and used in the experiments. The results showed that the average value of the pretest before applying the Problem Based Learning model was 70.77 with the percentage of completeness of student learning outcomes by 50% and the average posttest score after applying the Problem Based Learning model was 86.03 with the percentage of completeness of student learning outcomes amounted to 86.67%. The obtained Gain Score is 0.45 in the medium category. Based on these data, it is concluded that the use of Problem based learning (PBL) models can improve student learning outcomes in class XI TITL on Electric Power Installation subjects at SMK Negeri 2 Sijunjung.